“Life Is a Construction Site”: Cultural Studies Perspectives on Identity in Times of Geopolitical and Social Change (KULT_online, 2009)
Kultureller Umbau (Cultural Rebuilding) is a transdisciplinary, transcultural, and transmedial anthology edited by Meike Kröncke, Kerstin Mey, and Yvonne Spielmann that revolves around three central concepts in the study of culture: space, identity, and representation. All articles are based on the assumption that times of geopolitical and social transformation demand a new understanding of identity which takes into account our changing perceptions of spatial order – a process of transformation that the editors term “kultureller Umbau” (cultural rebuilding). Contributors delve into the three central concepts from the perspectives of media studies, cultural studies, art history, and sociology.